2003
DOI: 10.1086/368067
|View full text |Cite
|
Sign up to set email alerts
|

Motions of IsolatedG‐Band Bright Points in the Solar Photosphere

Abstract: Magnetic elements on the quiet Sun are buffeted by convective flows that cause lateral motions on timescales of minutes. The magnetic elements can be observed as bright points (BPs) in the G band at 4305 Å . We present observations of BPs based on a long sequence of G-band images recorded with the Dutch Open Telescope and postprocessed using speckle-masking techniques. From these images we measured the proper motions of isolated BPs and derived the autocorrelation function of their velocity relative to the sol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
79
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 33 publications
23
79
1
2
Order By: Relevance
“…Our internetwork features appear to live less long than (photospheric) network BPs which last on average 1080 s (Muller 1983), however, a comparable mean lifetime of 9.2 min for network GBPs was found by Nisenson et al (2003). In addition, we showed that the Ca ii H BPs move horizontally with an average speed of 2.2 km s −1 .…”
Section: Discussionmentioning
confidence: 46%
“…Our internetwork features appear to live less long than (photospheric) network BPs which last on average 1080 s (Muller 1983), however, a comparable mean lifetime of 9.2 min for network GBPs was found by Nisenson et al (2003). In addition, we showed that the Ca ii H BPs move horizontally with an average speed of 2.2 km s −1 .…”
Section: Discussionmentioning
confidence: 46%
“…Such short duration motions are expected to be generated by the turbulent motion in the convectively unstable subsurface layers where the flux sheet is rooted. In terms of the analysis by Cranmer & van Ballegooijen (2005) of the kinematics of G-band bright points, this motion rather corresponds to a short, single step of their "random walk phase", for which these authors use a rms velocity of 0.89 km s −1 with a correlation time of bright-point motions of 60 s in accordance with the measurements of Nisenson et al (2003). The cases with higher velocities (see Table 2) would rather be representative of the "jump phase" for which Cranmer & van Ballegooijen (2005) use a velocity of 5 km s −1 with a duration of 20 s. This motion generates magnetoacoustic waves in the flux sheet.…”
Section: Methods and Boundary Conditionsmentioning
confidence: 97%
“…However, network time scales are well known to vary substantially in the range from min to many hours (e.g. Liu et al 1994;Muller 1994;Berger & Title 1996;Berger et al 1998;Nisenson et al 2003).…”
Section: Autocorrelation Analysismentioning
confidence: 99%